ANALYSIS OF DIFFERENCE IN STOCK PRICE, MARKET CAPITALIZATION, AND TRADING VOLUME ACTIVITY BEFORE AND DURING COVID-19 - Suramin, Louis Vigo; Suhendah, Rousilita (International Journal of Application on Economics and Business, 2023)
The aim for this study is to find whether if there is a difference of stock price, market capitalization, and trading volume before and during COVID-19 pandemic on agriculture and mining sector. The data used for this research is taken from January 1st until April 30th 2020. The sampling technique used on this study was purposive sampling and processed using SPSS 25. The result shows that there are a difference between stock price before and during COVID-19, market capitalization before and during COVID-19, and trading volume before and during COVID-19 on both agriculture and mining sector.